Cephalometric predictors of hypernasality and nasal air emission - María Alicia DENEGRI; Patrick Pedreira SILVA; Maria Inês PEGORARO-KROOK; Terumi Okada OZAWA; Renato Yassutaka Faria YAEDU; Jeniffer de Cássia Rillo DUTKA (University of São Paulo, 2021)
Abstract During times of increasingly recognized importance of interprofessional practices, professionals in Medicine, Dentistry, and Speech Pathology areas cooperate to optimize treatment of velopharyngeal dysfunction (VPD), after primary palatoplasty for correction of cleft palate. Objective Our study aims to compare velar length, velar thickness, and depth of the nasopharynx of patients with unilateral cleft lip and palate (UCLP) with the presence, or absence, of hypernasality and nasal air emission; and to verify if the depth:length ratio, between nasopharynx and velum, would be predictive of consistent hypernasality and nasal air emission (speech signs of VPD). Methodology Cephalometric radiographs and outcome of speech assessment were obtained from 429 individuals, between 6 and 9 years of age, with repaired unilateral cleft lip and palate. Velar length, velar thickness, depth of the nasopharynx, depth:length ratio, scores of hypernasality, and scores of nasal air emission were studied and compared; grouping the radiographs according to presence or absence of hypernasality and nasal air emission. Results For the group with speech signs of velopharyngeal dysfunction (those with consistent hypernasality and nasal air emission), the velums were shorter and thinner; the nasopharynx was deeper and the depth:length ratio was larger than the group without hypernasality and nasal air emission. Velar length was significantly shorter in individuals with consistent hypernasality and nasal air emission (p<0.001) and with history of palatal fistula (p=0.032). Depth of nasopharynx was significantly greater in individuals with consistent hypernasality and nasal air emission (p<0.001). Depthlength ratio was significantly larger in individuals with consistent hypernasality and nasal air emission (p<0.001). A depth:length ratio larger than 0.93 was always associated with speech signs of VPD. Conclusion Estimated with cephalometric radiographs, a depth:length ratio greater than 0.93, between the nasopharyngeal space and the velum, was 100% accurate in predicting hypernasality and nasal air emission after primary repair of unilateral cleft lip and palate.